Determinan Kejadian Hipertensi Masyarakat Pesisir Berdasarkan Kondisi Sosio Demografi dan Konsumsi Makan - Nofi Susanti; Putra Apriadi Siregar; Reinpal Falefi (Sarana Ilmu Indonesia (salnesia), 2020)
Hypertension is still a public health problem, including in the coastal areas. Socio demographic dan unbalanced food consumptions in coastal communities becomes determinant of hypertension. The purpose of this study is to find out hypertension’s determinant in coastal communities based on socio demographic and food consumption. This research uses a descriptive-analytic method with cross-sectional study in December 2019 with a sample of 90 people using the chi-square test. The results showed a significant relationship between food consumption patterns (p = 0.009; POR = 3.780), educational status (p = 0.001; POR = 5.350), age (p = 0,000; POR = 9,000) The conclusion of the study is that there is a significant relationship between food consumption patterns, educational status and age of hypertension in the coastal areas of Percut Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. Suggestions for health workers to be able to increase efforts to promote health on an ongoing basis, especially for patients with hypertension.